Long-term safety and impact of immune recovery in heavily treatment-experienced adults receiving fostemsavir for up to 5 years in the phase 3 BRIGHTE study - Llibre, Josep M.; Aberg, Judith A.; Walmsley, Sharon; Velez, Juan; Zala, Carlos; Crabtree Ramírez, Brenda; Shepherd, Bronagh; Shah, Rimi; Clark, Andrew; Tenorio, Allan R.; Pierce, Amy; Du, Fangfang; et al. (Frontiers in Immunology, 2024)
Fostemsavir is a gp120-directed attachment inhibitor approved for heavily treatmentexperienced (HTE) adults with multidrug-resistant HIV-1. We provide detailed week 240 safety results from the BRIGHTE study and evaluate the impact of immune recovery on safety outcomes. Methods: The phase 3 BRIGHTE trial is ongoing; data for this analysis were collected from the first participant's first visit (February 23, 2015) through the last participant's last visit for week (March 22, 2021). Safety endpoints were assessed in participants who received fostemsavir + optimized background therapy. In participants with baseline CD4+ T-cell count <200 cells/mm 3 , exposure-adjusted adverse event (AE) rates were assessed among subgroups with or without CD4+ T-cell count ≥200 cells/mm 3 at any time during 48-week analysis periods through week 192. Results: Through a median of 258 weeks (range, 0.14-319) of treatment, discontinuations due to AEs occurred in 30/371 (8%) participants. Serious AEs were reported in 177/371 (48%) participants, including 16 drug-related events in 13 (4%) participants. Thirty-five (9%) deaths occurred, primarily related to AIDS or acute infections. COVID-19-related events occurred in 25 (7%) participants; all resolved without sequelae. Among participants with baseline CD4+ T-cell count <200 cells/mm 3 , 122/162 (75%) achieved CD4+ T-cell count ≥200 cells/mm 3 at week 192. Exposure-adjusted AE rates were markedly lower among participants achieving CD4+ T-cell count ≥200 cells/mm 3 at any time vs those sustaining <200 cells/mm 3 . No new AIDS-defining events were reported after week 48 in participants with CD4+ T-cell count ≥200 cells/mm 3 . Conclusions: Cumulative safety findings through the BRIGHTE 240-week interim analysis are consistent with other trials in HTE participants with advanced HIV-1 and comorbid disease. Reduced rates of AIDS-defining events and AEs were observed in participants with immunologic recovery on fostemsavir-based treatment. Clinical trial number: NCT02362503, https://clinicaltrials.gov/study/NCT02362503.